Creation and Evaluation of Fungal Mutants. ALE, Mutagenesis and High Throughput Screening - Martinsson Budillon , Emil (My University)
Climate change is becoming an ever-approaching issue and there has never been a better time for various industries to radically alter their production processes to reduce environmental pollutants. One of these industries that is among the most polluting food sources is the dairy industry. Where an unorthodox alternative to cattle could be to use filamentous fungi to produce the components of milk, such as casein, and mixing them together. Thereby creating a vegan milk alternative with the same nutrients content as the animal derived version. To further lessen the environmental impact the fungi could be cultivated on an industrial by-product. Increasing fermentation yields would require strain development to raise substrate tolerance, change morphology and remove casein degradation. The aim was to develop strains from two fungi using random mutagenesis to increase substrate tolerance and reduce the ability to degrade casein and adaptive laboratory evolution to increase substrate tolerance while at the same time changing morphology towards a more dispersed morphology. Random mutagenesis showed that an exposure time of at least 9 and 8 min of exposure to UV, respectively caused a survival rate of less than 1 % and resulted in changes in growth on industrial media as well as on casein. Adaptive laboratory evolution resulted in an increase in media tolerance of 25 % and 100 % for the respective fungi, while also changing the morphology to smaller mycelial clumps. Due to issues related to producing spores an incomplete screening was made of the mutants generated during this experiment. These results clearly indicate that random mutagenesis and adaptive laboratory evolution show great potential as methods for further developing the industrial use of filamentous fungi.
Keywords: Random; Mutagenesis; ALE; High; Throughput; Screening; Morphology; Filamentous; Fungi